METODE PELAKSANAAN PEMBANGUNAN TEROWONGAN BENDUNGAN WAY APU MENGGUNAKAN NATM (NEW AUSTRIAN TUNNELING METHOD) - ACUN (Jurusan Teknik Sipil, 2024)
The advancement and development of science and technology in various fields have a positive impact on the development of construction technology. NATM is a tunnel manufacturing system using Shocrete and rockbolt as temporary support for the tunnel before being given a layer of concrete. The purpose of this study is to determine the proper and efficient implementation of the construction of the Way Apu Dam Dodge Tunnel using NATM and find out the types of work on the Way Apu Dam Dodge Tunnel using NATM. The object of this study is the way Apu Dam circumvention tunnel. The primary and secondary data are used. The results of this study we can find out the types of work carried out using the NATM method, namely: field survey work, and open land excavation work, which has several stages, namely mobilization and demobilization, Clearning and Grubing work, Inlet and Outlet open land excavation work. After the next open ground excavation work, tunnel excavation work. Tunnel excavation uses two methods of excavation, namely blasting and mechanical methods. The blasting method has stages: preparatory work, drilling work, and blasting filling work. While the mechanical method has many jobs, namely preparatory work, marking work, temporary portal work, tunnel excavation work which also has a job title, namely, marking tunnel excavation, stages of survey implementation, excavation work, Mucking work, Scaling work, Ventilating work, Steel Rib work, Wiremesh work, Shotcrete work, Rockbolt work, LSPF work, dewatering work. And Concrete Lining work.